Differential Study of Antimicrobial Activity of Vancomycin and Teicoplanin (Targocid) against Strains of Staphylococcus aureus and Streptococci sp. - Ali Hasan, Waseem (Tikrit Journal of Pharmaceutical Sciences, 2023)
The glycopeptide antibiotics vancomycin and teicoplanin (targocid) are widely used in the treatment of infections caused by gram positive bacteria. Vancomyc inhibits both transglycosylation and transpeptidation reaction during peptidoglycan assembly, targocid inhibits peptidoglycan polymerization, resulting in inhibition of bacterial cell wall synthesis and cell death. In this study twenty strains of streptococcus pyogenes and streptococcus pneumoniae and twenty five strains of staphylococcus aureus were collected from different infections. MI Cs and MBCs of vancomycin and targocid were determined against the bacterial strains, the MICs of vancomycin for the streptococcus strains were 4-8 µg /ml compared with 8-16 µg/ml for targocid and MI Cs of targocid for staphylococcus aureus were 4-16 µg/ml MBC for the same strains were 8-32 µg/ml. the conclusion of this study was that targocid was less active than vancomycin against staphylococci but equal or more active against streptococci specifically it presents excellent in vitro activity against streptococcus pneumonia strains.